Intralingual Translation Procedures in Nihon NO Uta - Amri, Miftachul; Rusmiyati, Rusmiyati; Adhimas, Yogi Bagus; Birri, Iffa Mar’atus Shohibul; Zulmi, F A. Z.; Irawati, Fitriana Dewi (Yayasan Gema Bina Nusantara, 2024)
The purpose of this study is to analyze how intralingual translation procedures are used in translating modern Japanese songs into classical Japanese. This study used a descriptive qualitative method with Vinay and Darbelnet's translation procedures theory to explain the process of intralingual translation. The results of the study showed that the song translated influenced the use of translation procedures. For example, the song